2021
DOI: 10.18231/j.ijirm.2021.003
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of chest radiographic abnormalities and co-morbidities in newly detected sputum positive pulmonary tuberculosis cases

Abstract: Background: Tuberculosis (TB) is an airborne communicable disease which one of the leading causes of morbidity and deaths worldwide (ranking above AIDS).1 Probability of detecting AFB on sputum is greatly associated by the radiological findings.8 Because of the apparent widespread difficulty in recognizing the radiographic manifestations of pulmonary tuberculosis, it will be beneficial to review the spectrum of chest x-ray abnormalities in sputum positive tuberculosis patients. Aim: To study clinical features,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Our study reported that lower zone involvement in chest X-ray was significantly higher (Fisher’s exact test p-value = 0.0079) in pulmonary TB with DM (17/20, 85%) compared to pulmonary TB without DM group (8/20, 40%). Multiple previous studies showed the same atypical finding in chest X-rays [ 2 , 8 - 13 , 23 , 24 ]. However, several other studies showed similar radiological findings in both groups [ 14 - 17 , 25 ].…”
Section: Discussionsupporting
confidence: 64%
“…Our study reported that lower zone involvement in chest X-ray was significantly higher (Fisher’s exact test p-value = 0.0079) in pulmonary TB with DM (17/20, 85%) compared to pulmonary TB without DM group (8/20, 40%). Multiple previous studies showed the same atypical finding in chest X-rays [ 2 , 8 - 13 , 23 , 24 ]. However, several other studies showed similar radiological findings in both groups [ 14 - 17 , 25 ].…”
Section: Discussionsupporting
confidence: 64%